О. П. Іваніцька. Франкістська Іспанія 1939-1975 рр.: історіографія - Копилов, С. А. (Український історичний журнал, 2025)
О. П. Іваніцька. Франкістська Іспанія 1939-1975 рр.: історіографія. — Вінниця, 1996. — 160 с.